Characteristics influencing international students’ information search and satisfaction on private higher education institution in Malaysia / Nurlida Ismail - Ismail, Nurlida (2013)
The intensifying mobility of international students and competition among private higher education institutions has augmented the need for understanding these students choice process. Information search as an initial stage of the choice process has been the topic of much research. A more challenging area of study is the relationship between international students' information search and satisfaction on a private higher education institution. However, literature has revealed that the study on this relationship, specifically in the Malaysian 'scenario, has been very scarce. Hence, this study aims to address this knowledge gap and attempts to extend previous study on information search by integrating satisfaction constructs into the framework. Data collection commenced for 2009 to 2010 and there were 187 private education institutions enrolling international students. Of that, only 32 institutions responded and participated in the study. A proportionate sampling was employed whereby international students were divided according to the population and the status of the institutions. Structured questionnaire was used and two pilot studies were administered to refine the items in the scales using SPSS version 17. For the final study, to ensure a more rigorous analysis, structural equation modeling using AMOS 18 was employed to empirically test the effects of the respective predictors on latent variables. Results indicated that out of the nine hypotheses formulated, seven hypotheses were supported at five percent significant level. A significant finding is that information characteristics (institution attributes and information accessibility) were the most important predictors of information search and information satisfaction. A major contribution to the advancement of new knowledge is that the results also emphasized that information satisfaction in turn, is a significant mediator in the relationship between student characteristics (knowledge and involvement), institution characteristics (perceived risk) and information characteristics (institution attributes and accessibility) with institution choice satisfaction. This is a timely study as the results have addressed issues on strengthening the private education services sectors in line with the Economic Transformation Programme (ETP) effort. The study provides mechanisms for institutions to enhance their promotional programs and formulation of policies in improving their international students' enrolment. In addition, findings are of significance to the Government in strengthening its position to successfully transform Malaysia as the "major education centre of choice and a pivotal hub in the global education network". Findings may assist institutions and the Government in understanding the multiple influences of information search affecting international students' choice. By allocating resources to these key factors, their communication and promotional efforts can be further enhanced. This will increase students' motivation to search and eventually lead to the selection of these institutions as their preferred destination. This study also contributes to the development of an empirical basis for future study on international students' choice of institution.